The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/er.4834
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hetero‐elements doping content in biomass waste‐derived carbon for high performance supercapacitor

Abstract: Summary Betel nut wastes are firstly modified with nitric acid/thiourea to fabricate hetero‐element doping carbon (C‐H‐T) for energy storage. C‐H‐T exhibits improved content of O (12.27%), N (2.52%), and S (2.88%) compared with that of purely carbonized carbon with O (9.2%) and N (1.76%). Without nitric acid heat treatment, the carbon materials prepared by hydrothermal treatment with thiourea only get increasing hetero‐elements content of O (10.46%), N (2.9%), and S (0.53%). The similar results have been obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…The internal resistance of the CoMoO 4 electrodes is smaller than numerous fabricated metal oxide-based electrodes. [8][9][10]16,32,49 Moreover, Miroshnikov et al 79 and Fang et al 76 demonstrated outstanding capacitive behaviour by EIS analysis of organic compounds and biomass-carbon based electrodes, respectively, due to the C, H, N, and O atoms of the electrode material. Therefore, in the current study, the low internal resistance was strongly attributed to the fact that the pathways for electron transport were not only provided by Mo and Co, but also the organic stabilizing agents (C 4 H 8 O and C 8 H 19 N) of CoMoO 4 as indicated by XPS ( Fig.…”
Section: Supercapacitive Studiesmentioning
confidence: 99%
“…The internal resistance of the CoMoO 4 electrodes is smaller than numerous fabricated metal oxide-based electrodes. [8][9][10]16,32,49 Moreover, Miroshnikov et al 79 and Fang et al 76 demonstrated outstanding capacitive behaviour by EIS analysis of organic compounds and biomass-carbon based electrodes, respectively, due to the C, H, N, and O atoms of the electrode material. Therefore, in the current study, the low internal resistance was strongly attributed to the fact that the pathways for electron transport were not only provided by Mo and Co, but also the organic stabilizing agents (C 4 H 8 O and C 8 H 19 N) of CoMoO 4 as indicated by XPS ( Fig.…”
Section: Supercapacitive Studiesmentioning
confidence: 99%
“…In recent times, increasing reliance on renewable energies has forced the scientists and engineers to developed efficient and cost effective storage systems for renewable energies . Supercapacitors (also known as electrochemical capacitors) have gained extensive research focus in the field of energy storage due to reasonable high power density, quick charging and discharging, safe operation, and optimum working conditions . The performance of a capacitor is critically depending on its electrode .…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors (also known as electrochemical capacitors) have gained extensive research focus in the field of energy storage due to reasonable high power density, quick charging and discharging, safe operation, and optimum working conditions . The performance of a capacitor is critically depending on its electrode . Therefore, over recent years, the development of efficient supercapacitor electrode is the focus of attention among researcher …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HNO 3 activation process promotes some complex reactions which can increase the polarity, pores and SSA, indicating sufficient ion transmission channels and electrochemical active sites [44,45]. The KOH activation process optimizes the pore structure and increases the SSA of the biomass-derived carbon precursors by removing the non-carbon atoms, etching the surface, and generating vast pores [46][47][48]. The followed electrochemical measurements confirmed the right choice of the activation order ( Figure S1).…”
Section: Resultsmentioning
confidence: 69%